Diversity in pediatric behavioral sleep intervention studies. (October 2019) - Schwichtenberg, Amy J.; Abel, Emily A.; Keys, Elizabeth; Honaker, Sarah M.
Summary: Studies designed to assess the efficacy of behavioral sleep interventions for infants and young children often report sleep improvements, but the generalization to children and families of diverse backgrounds is rarely assessed. The present study describes a systematic review of the racial, ethnic, and socioeconomic diversity of behavioral sleep intervention studies for young children. Thirty-two behavioral sleep intervention studies (5474 children) were identified using PRISMA guidelines. Each study was coded for racial and ethnic composition, parental educational attainment (an index of socioeconomic resources), and country of origin. Racial or ethnic information was obtained for 19 studies (60%). Study participants were primarily White and from predominantly White countries. Overall, 21 (66%) of the included studies provided information on parental education. Most of these studies had samples with moderate to high educational attainment. Behavioral sleep intervention studies to date include samples with insufficient diversity. Overall, this study highlights a critical gap in pediatric sleep intervention research and supports a call to further include families from diverse backgrounds when assessing behavioral sleep interventions.